Crystal structures of human neuropeptide Y (NPY) and peptide YY (PYY). (April 2022) - Langley, David B.; Schofield, Peter; Jackson, Jenny; Herzog, Herbert; Christ, Daniel
Abstract: Neuropeptide Y (NPY), peptide YY (PYY) and pancreatic polypeptide (PP) form the evolutionarily conserved pancreatic polypeptide family. While the fold is widely utilized in nature, crystal structures remain elusive, particularly for the human forms, with only the structure of a distant avian form of PP reported. Here we utilize a crystallization chaperone (antibody Fab fragment), specifically recognizing the amidated peptide termini, to solve the structures of human NPY and human PYY. Intriguingly, and despite limited sequence identity (~50%), the structure of human PYY closely resembles that of avian PP, highlighting the broad structural conservation of the fold throughout evolution. Specifically, the PYY structure is characterized by a C-terminal amidated α-helix, preceded by a backfolded poly-proline N-terminus, with the termini in close proximity to each other. In contrast, in the structure of human NPY the N-terminal component is disordered, while the helical component of the peptide is observed in a four-helix bundle type arrangement, consistent with a propensity for multimerization suggested by NMR studies.